2020
DOI: 10.1039/c9rp00077a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of basic arithmetic skills on success in first-semester general chemistry

Abstract: First-semester general chemistry is a known “gatekeeper” course due to its high failure rate. These higher education courses are taken by students who for the most part are regularly admitted freshmen, yet many struggle to succeed. In this investigation researchers from six higher-education institutions of varied sizes with student bodies of different ethnic composition teamed up to investigate the Math-Up Skills Test (MUST) as a potential tool to identify at-risk students in first-semester general chemistry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 45 publications
(64 reference statements)
4
32
0
Order By: Relevance
“…(2017) identified calculus as a "choke point" barrier to STEM success. Mathematics level completed was a powerful determinant for success in an introductory chemistry class in other research studies as well (Mason & Mittag, 2001;Petros et al, 2017;Williamson et al, 2020), where the higher the mathematics level completed, the higher the student's course average. Sax (2017) reported the top explanatory gender-gap variable for computer science students was mathematics skills where women rated themselves lower than men but this gap was weakening over the period of the study .…”
Section: Literature Reviewmentioning
confidence: 81%
See 1 more Smart Citation
“…(2017) identified calculus as a "choke point" barrier to STEM success. Mathematics level completed was a powerful determinant for success in an introductory chemistry class in other research studies as well (Mason & Mittag, 2001;Petros et al, 2017;Williamson et al, 2020), where the higher the mathematics level completed, the higher the student's course average. Sax (2017) reported the top explanatory gender-gap variable for computer science students was mathematics skills where women rated themselves lower than men but this gap was weakening over the period of the study .…”
Section: Literature Reviewmentioning
confidence: 81%
“…While some students self-identified as non-binary for gender, this group was too small to report on while maintaining confidentiality. Previous studies by the Networking for Science Advancement (NSA) team have reported that students' automaticity ability (what can be done without the aid of a calculating device), as measured by an easily administered diagnostic test named the MUST (Math-Up Skills Test), correlates well with students' success in general chemistry courses (Albaladejo et al, 2018;Mamiya et al, in press;Petros et al, 2017;Powell et al, 2020;Villalta-Cerdas et al, in press;Weber et al, 2020;Williamson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of how confident in career choice they report, their preparation for their courses (i.e., their prior knowledge) is of upmost importance to having a more successful outcome. When they enter with low automaticity ability (what they can do without a calculator), they lack the mental-math skills that provide them with the ability to answer and complete problems they are likely to encounter in their general chemistry studies without struggling with the basic arithmetic skills as identified by the MUST, an excellent known predictor of course outcomes [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…The A copy of the MUST and answers are available from a previous publication [6]. The MUST has a very large Cohen's d effect size of 1.43 and 1.20 for Chem I and II, respectively.…”
Section: Diagnostic Instrumentmentioning
confidence: 99%
See 1 more Smart Citation